2006
DOI: 10.1093/pubmed/fdi065
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic deprivation, coronary heart disease prevalence and quality of care: a practice-level analysis in Rotherham using data from the new UK general practitioner Quality and Outcomes Framework

Abstract: Practice-level CHD prevalence is associated with deprivation, but we found no evidence of socioeconomic inequality in CHD care. This finding is in contrast to that from previous studies and the widely reported inverse care law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…[22][23][24][25] This is not to deny that deprived populations may face particular disadvantages in gaining access to high quality primary care. Several studies suggest that general practices located in areas of socioeconomic deprivation provide a lower quality of care as judged by QOF scores [26][27][28][29][30] (although it should be acknowledged that other studies find little evidence of socioeconomic inequality 31,32 ). There may also be plausible reasons why, relative to underlying morbidity, deprived groups need greater access to primary care.…”
Section: Original Papers Discussion Papermentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25] This is not to deny that deprived populations may face particular disadvantages in gaining access to high quality primary care. Several studies suggest that general practices located in areas of socioeconomic deprivation provide a lower quality of care as judged by QOF scores [26][27][28][29][30] (although it should be acknowledged that other studies find little evidence of socioeconomic inequality 31,32 ). There may also be plausible reasons why, relative to underlying morbidity, deprived groups need greater access to primary care.…”
Section: Original Papers Discussion Papermentioning
confidence: 99%
“…For example, there appears to be a greater readiness on the part of disadvantaged people to consult GPs, perhaps due to a lack of confidence in self-management. [31][32][33][34][35] This, together with higher levels of psychological distress would be expected to place higher demands on primary care practitioners working in deprived areas. 36,37 The point, then, is not to dismiss the legitimate healthcare needs that arise from deprivation but to recognise that evidence on inequalities in the provision of GPs is more complex and equivocal than implied by the Darzi interim report.…”
Section: Original Papers Discussion Papermentioning
confidence: 99%
“…This information is then brought together into one overall IMD score, which was initially done in 2000. The indices are used widely to analyze patterns of socioeconomic deprivation and relationships with several health outcomes to identify areas that would benefit from special initiatives or programs of action for health and development (15)(16)(17)(18)(19)(20).…”
Section: Measures Of Sesmentioning
confidence: 99%
“…By using proxy measures, it is also likely that the role of ethnicity and social deprivation in determining health inequalities has been underestimated. 10 The study analysis was confined to mortality reduction. Arguably, the impact of primary care is likely to be greater in terms of improving quality-adjusted life years or reducing disability-adjusted life years, but this study, like others, found few data to conduct such an analysis.…”
Section: Strengths and Limitationsmentioning
confidence: 99%